2009
DOI: 10.1080/10901020903084330
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Quality of Early Childhood Education in China: Implications for Early Childhood Teacher Education

Abstract: The following article introduces an exploratory study that was designed to measure the quality of early childhood education within its ever changing sociocultural context utilizing the Early Childhood Learning Environment Rating Scale-Revised (ECERS-R) in 40 classrooms in Beijing, China. Implications for early childhood teacher education, including the education of children with exceptional needs are addressed along with recommendations for future research.The development of Chinese early childhood education i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 14 publications
1
30
0
6
Order By: Relevance
“…Last, outdoor play typically refers to the use of large stationary equipment, such as tricycles, and portable toys, such as balls of all sizes, in either free play or a teacher-led activity. Hu and Szente (2009a) found that, due to large class sizes, as well as limited equipment and space, outdoor play time was divided between free play and teacher-led games. "Eagle Catches Chicken" is one example of popular teacher-led outdoor play-the teacher plays the eagle (while supervising the activity) and the children play chickens.…”
Section: Chinese Early Childhood Practices Related To Physical Activimentioning
confidence: 99%
“…Last, outdoor play typically refers to the use of large stationary equipment, such as tricycles, and portable toys, such as balls of all sizes, in either free play or a teacher-led activity. Hu and Szente (2009a) found that, due to large class sizes, as well as limited equipment and space, outdoor play time was divided between free play and teacher-led games. "Eagle Catches Chicken" is one example of popular teacher-led outdoor play-the teacher plays the eagle (while supervising the activity) and the children play chickens.…”
Section: Chinese Early Childhood Practices Related To Physical Activimentioning
confidence: 99%
“…Teachers became important professionals since the 1980s but early childhood education was given importance only in the latest decade (Hu & Szente, 2009;Wu, Young & Cai, 2012).The initial emphasis of professional development of early childhood teachers was on developing their musical and artistic skills which could distinguish early childhood teachers from those in school sectors and establish early childhood education as a special stage in children's development (New & Cochran, 2007).…”
Section: Professional Development In Early Childhood Education In Chimentioning
confidence: 99%
“…Others (Hu & Szente, 2009) discuss the pressure caused by academic competition and parents' preference for academic learning. In brief, while scholars accept that liberal beliefs relating to such issues as individualism have been incorporated into the curriculum, many features that are uniquely Chinese remain intact (Vong, 2008;Wong & Pang, 2002).…”
Section: The Literaturementioning
confidence: 99%